Uncovering the nexus between earnings management and dividend policies: Evidence from unlisted firms in Portugal - Lopes, A.I.; Narciso, A. (13th Portuguese Finance Network Conference, 2025)
Earnings quality is frequently studied, but its relationship with dividend policies in unlisted companies is rarely studied. This study expands research on financial reporting quality in companies unaffected by market pressures but whose financial statements are important for tax and dividend requirements. Dividend agency models are expanded in this paper to include unlisted corporations. The findings demonstrate that earnings management strategies enhance dividend policy, but only when ownership concentration is high, under a single stakeholder's control, and there is no signed earnings management. This supports the alternative model of the agency theory of dividends. A positive (negative) influence of earnings management on dividend policy is shown when earnings are managed downward (upward), in line with the substitution (outcome) model. Taxes are essential in clarifying these links. We found that unlisted corporations frequently use the substitution model of agency theory for dividends, unless they pay income taxes and inflate earnings